Article RETRACTED due to manipulation by the authors Unlocking the Science of Physical Endurance: Training Techniques and Biological Factors - Yendrizal Yendrizal; Ardo Okilanda; Masrun Masrun; M Ridwan; Mottakin Ahmed; Silvio Crisari; Singha Tulyakul (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study examines the many elements influencing endurance performance in university students, including training routines, psychological fortitude, hereditary tendencies, and environmental adjustments. Data was gathered from 38 university students engaged in endurance sports using a descriptive methodology. The results reveal a significant commitment to endurance training since individuals typically participate in four sessions each week, each lasting around 60 minutes. Psychological resilience plays a significant role, with 82% of participants showing strong levels of intrinsic motivation and 74% displaying mental toughness in overcoming obstacles. 37% of participants have a family history of endurance performance, while 29% are interested in genetic testing, showing differing views on hereditary effects on performance. Performance outcomes are greatly impacted by environmental conditions, such as altitude training (42%), and heat acclimatisation (63%), which are often used tactics. The physiological examinations show an average VO2 max of 50 ml/kg/min, along with a muscle fibre composition consisting of 55% slow-twitch fibres and 45% fast-twitch fibres. The results highlight the intricate nature of elements influencing endurance performance in university students, emphasising the need for customised support systems. Universities can enhance performance outcomes and foster comprehensive athlete development by considering physiological, psychological, genetic, and environmental factors. This study enhances comprehension of the complex aspects of endurance performance in university students, offering valuable insights for improving athletic training and support programmes. Coaching recommendations should customise training programmes based on individual athlete requirements, utilising strong intrinsic motivation and mental resilience to create a favourable training atmosphere and enhance performance results.